EuReCa_Serbia 2014-2023 Time from call to arrival at the scene of the accident - impact on the initiation of CPR measures - Lazic, Aleksandra; Vasilic, Milica; Medic, Sara (Journal Resuscitatio Balcanica, 2024)
Introduction: The rate of non-initiation of cardiopulmonary resuscitation (CPR) in patients with out-of-hospital cardiac arrest (OHCA) varies widely across countries, with limited findings in the literature addressing factors associated with higher rates of non-initiation, particularly reaction time (RT) of the emergency medical service team. The aim of this study is to analyze the data on RV length in relation to the initiation or non-initiation of CPR, including the collapse location, OHCA etiology, and the patient ageas additional factors potentially related to the frequency of CPR non-initiation.Material and Methods: In this study, data on initiation and non-initiation of CPR measures, length of RV, collapse location, OHCA etiology, and age of patients were collected and analzyedaccording to the protocol of the EuReCa study during the period October 1, 2014 - December 31, 2023.Results: A total of 10458 EuReCa events with a median RV of 9 (IQR 5-17) minutes were recorded during the follow-up period. In 6197/10458 cases (59.3%) CPR measures were not initiated. Statistically significantly longer RV was observed in the group of patients in whom CPR measures were not initiated, compared to cases where those were applied (Med = 25 (IQR 10-45) vs. Med = 6 (IQR 4-10) minutes, respectively); p
Keywords: out-of-hospital cardiac arrest; cardiopulmonary resuscitation; CPR reaction time; surviving out-of-hospital cardiac arrest.